IMPLEMENTASI KEBIJAKAN PERLINDUNGAN KETENAGAKERJAAN UNTUK MENINGKATKAN KESEJAHTERAAN PEKERJA - Darmawan, Muhamad Adi; Fatriani, Fennny (LPPM Universitas Bina Bangsa, 2025)
Employment is an important aspect in the economic and social development of a country. In Indonesia, employment protection policies aim to guarantee workers' basic rights, create a safe and healthy work environment, and provide legal certainty in industrial relations. The Indonesian government has established various employment regulations, such as Law Number 13 of 2003 concerning Employment and policies related to social security through BPJS Employment and wage policies. This policy is expected to improve worker welfare and reduce risks in the world of work. However, the implementation of this policy in the field often faces various challenges, ranging from lack of supervision, company non-compliance, to workers' lack of understanding of their rights. This article will review how existing employment protection policies in Indonesia are implemented, the challenges faced in their implementation, as well as strategies for optimizing these policies so that they can contribute directly to improving worker welfare.